Less feed does not mean lower growth: The impact of feeding frequency on fishes reared in BFT enriched with sodium chloride - Thiago Marinho-Pereira; Bruno Adan Sagratzki Cavero; Christiane Patrícia Feitosa de Oliveira; Paulo Henrique Rocha Aride; Adriano Teixeira de Oliveira (Revista Brasileira de Zootecnia)
ABSTRACT The objective of this work was to analyze the impact of different feeding frequencies on the growth and hematological parameters of freshwater fish species (tambaqui, Colossoma macropomum; matrinxã, Brycon amazonicus) subjected to biofloc technology enriched with sodium chloride. We tested two feeding frequencies: T1 = feeding all experimental days for tambaqui, except on Sundays; T2 = feeding all experimental days for tambaqui, except on Sundays and Wednesdays; M1 = feeding all experimental days for matrinxã, except on Sundays; and M2 = feeding all experimental days for matrinxã, except on Sundays and Wednesdays. The growth performance of tambaqui and matrinxã were not affected by the treatments. The MCHC for matrinxã was the only hematological parameter significantly different. The physiological status (Kn = condition factor) of the M2 treatment was the only parameter that presented a significant difference in relation to the central value (Kn = 1.00). Water quality parameters remained within the range indicated for the rearing of both species. The feeding frequencies tested do not negatively affect tambaqui or matrinxã.